1994
DOI: 10.1002/j.1550-8528.1994.tb00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Selection of Ideal Body Size by Adolescent Females

Abstract: Cultural differences may partially account for the fact that more black women than white women are overweight in the United States. This study measured perceptions of ideal body size among 93 black and 80 white females, 14-17 years old, who were randomly selected from three public high schools in a southeastern state. The subjects' height and weight were measured along with their estimates of their mother's body size, weight control attitudes, and demographic variables.Blacks preferred a significantly larger b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 14 publications
4
42
0
Order By: Relevance
“…Future research must also examine the underlying moderators of the self-esteem and body weight change relationship. Since ethnic and socioeconomic factors are strongly related to obesity and body weight/shape norms (1,30,37), ethnic and socioeconomic factors, their relationship to obesity onset and to behavioral factors related to obesity; will be important variables to explore in future research. Changes in selfesteem over time in relationship to obesity onset, duration and severity should also be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Future research must also examine the underlying moderators of the self-esteem and body weight change relationship. Since ethnic and socioeconomic factors are strongly related to obesity and body weight/shape norms (1,30,37), ethnic and socioeconomic factors, their relationship to obesity onset and to behavioral factors related to obesity; will be important variables to explore in future research. Changes in selfesteem over time in relationship to obesity onset, duration and severity should also be examined.…”
Section: Discussionmentioning
confidence: 99%
“…The empirical literature supports the premise that Black women diet less and have less weight concern and body dissatisfaction than White women (Akan & Grilo, 1995;Flynn & Fitzgibbon, in press;Wilson, Sargent, & Dias, 1994). The lower incidence of restrictive eating and less rigid body image ideals may result in lower rates of anorexia and bulimia nervosa in Blacks when compared to Whites (Abrams, Allen, & Gray, 1993).…”
Section: Introductionmentioning
confidence: 86%
“…Rucker and Cash (37) reported scores from tests to assess body image in 104 black and white female college students in Virginia and found that the black students held more favorable body image attitudes than white on both global and weight-related body image. Wilson et al (50), using the technique of identification of silhouettes, found that black adolescent girls in South Carolina (n = 175) identified a larger silhouette as ideal than did white girls. Other studies have also reported less dieting or dietary restraint in black- American compared with white-American girls (22,37,45), although studies in adults do not always support this trend (2,7,43,49).…”
Section: Discussionmentioning
confidence: 99%